A homozygous CaSR mutation causing a FHH phenotype completely masked by vitamin D deficiency presenting as rickets - Szczawinska, Dorothea; Schnabel, Dirk; Letz, Saskia; Schöfl, Christof (Journal of Clinical Endocrinology and Metabolism, 2014)
Heterozygous inactivating calcium-sensing receptor (CaSR) mutations lead to familial hypocalciuric hypercalcemia (FHH), whereas homozygous mutations usually cause neonatal severe hyperparathyroidism.The objective of the study was to investigate the pathophysiological mechanisms of a homozygous inactivating CaSR mutation identified in a 16-year-old female.Clinical, biochemical, and genetic analyses of the index patient and her family were performed. Functional capacity of CaSRQ459R and CaSR mutants causing FHH (Q27R, P39A, S417C) or neonatal severe hyperparathyroidism (W718X) was assessed. Activation of the cytosolic calcium pathway and inhibition of PTH-induced cAMP signaling were measured.A 16-year-old girl presented with adolescent rickets, vitamin D deficiency, and secondary hyperparathyroidism. Vitamin D treatment unmasked features resembling FHH, and genetic testing revealed a homozygous CaSRQ459R mutation. Two apparently healthy siblings were homozygous for CaSRQ459R and had asymptomatic hypercalcemia and hypocalciuria. The CaSRQ459R mutation leads to mild functional inactivation in vitro, which explains the FHH-like phenotype in homozygous family members and the grossly exaggerated PTH response to vitamin D deficiency in the index case. The patient's parents and two other siblings were heterozygous, had normal serum calcium and PTH, but had marked hypocalciuria, which appeared to be associated with impaired in vitro activation of the calcium signaling pathway by CaSRQ459R. The Q459R mutation responded well to calcimimetic treatment in vitro.CaSR mutations causing mild functional impairment can lead to FHH, even in homozygous patients. The skeletal deformities in the index case were mainly due to severe vitamin D deficiency, and the CaSR mutation did not appear to have played a major independent role in the skeletal phenotype.
EVALuna2:1905